Pengaruh Kualitas Informasi, Persepsi Kebermanfaatan, Persepsi Kemudahan Dan Computer Self Efficacy Terhadap Minat Menggunakan Internet(Studi Empiris Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Pramujati, Etika Putri Indah, Dr, Fatchan Achyani, SE, M.Si (2017)
Abstract The purpose of this study was to examine the effect of the quality information, perceived usefullnes, perceived ease of use, and computer self efficacy on the intention to use internet. The research was conducted in major Accounting Faculty Economic and Business Muhammadiyah University of Surakarta. Determination of sample, using a convenience sampling method.The data in this research is obtained by distributing questionnaires to the respondents. The number of respondents as many 100 people. The data analysis was using multiple linear regressions analysis. The analysis showed quality information, perceived usefullnes, perceived ease of use, and computer self efficacy have a significant effect on the intention of the intention to use internet. Key words : quality information, usefullnes,perceived ease of use, computer self efficacy,intention to use